Mechanistic and biophysical characterization of polymyxin resistance response regulator PmrA in Acinetobacter baumannii - Ouyang, Zhenlin; He, Wenbo; Jiao, Min; Yu, Qinyue; Guo, Yucheng; Refat, Moath; Qin, Qian; Zhang, Jiaxin; Shi, Qindong; Zheng, Fang; Wen, Yurong (Frontiers in Microbiology, 2024)
Introduction: Acinetobacter baumannii PmrAB is a crucial two-component regulatory system (TCS) that plays a vital role in conferring resistance to polymyxin. PmrA, a response regulator belonging to the OmpR/PhoB family, is composed of a C-terminal DNA-binding effector domain and an N-terminal receiver domain. The receiver domain can be phosphorylated by PmrB, a transmembrane sensor histidine kinase that interacts with PmrA. Once phosphorylated, PmrA undergoes a conformational change, resulting in the formation of a symmetric dimer in the receiver domain. This conformational change facilitates the recognition of promoter DNA by the DNA-binding domain of PmrA, leading to the activation of adaptive responses. Methods: X-ray crystallography was carried out to solve the structure of PmrA receiver domain. Electrophoretic mobility shift assay and Isothermal titration calorimetry were recruited to validate the interaction between the recombinant PmrA protein and target DNA. Field-emission scanning electron microscopy (FE-SEM) was employed to characterize the surface morphology of A. baumannii in both the PmrA knockout and mutation strains. Results: The receiver domain of PmrA follows the canonical α5β5 response regulator assembly, which undergoes dimerization upon phosphorylation and activation. Beryllium trifluoride is utilized as an aspartate phosphorylation mimic in this process. Mutations involved in phosphorylation and dimerization significantly affected the expression of downstream pmrC and naxD genes. This impact resulted in an enhanced cell surface smoothness with fewer modifications, ultimately contributing to a decrease in colistin (polymyxin E) and polymyxin B resistance. Additionally, a conservative direct-repeat DNA PmrA binding sequence TTTAAGNNNNNTTTAAG was identified at the promoter region of the pmrC and naxD gene. These findings provide structural insights into the PmrA receiver domain and reveal the mechanism of polymyxin resistance, suggesting that PmrA could be a potential drug target to reverse polymyxin resistance in Acinetobacter baumannii.